THE EFFECTIVENESS OF GAMIFICATION AND DIDACTIC GAMES IN ENGINEERING GRAPHICS EDUCATION - Mashrapova Gulbakhor Mamasaliyevna (Western European Studies, 2025)
This article investigates the effectiveness of gamification and didactic games in engineering graphics education. Through a review of international literature, curriculum analysis, intervention case studies, and stakeholder interviews, the study demonstrates that gamified and game-based learning significantly improve student engagement, motivation, and technical skill acquisition. Results show higher test scores, increased completion rates, and positive attitudes among students exposed to these methods. The discussion highlights the need for thoughtful game design, teacher training, and institutional support for sustainable adoption. The article concludes that gamification and didactic games are valuable strategies for modernizing engineering graphics pedagogy and building a more motivated, proficient engineering workforce.
Keywords: didactic games; Gamification; engineering graphics education